KEBAHAGIAAN DALAM PERSPEKTIF AL-QUR’AN DAN FILSAFAT - Khairul Hamim (Universitas Islam Negeri (UIN) Mataram, 2016)
Seeing from some perspectives, happiness has not reach finish line yet since it is very different and varied amongst the religions. The term ‘happy’ or ‘happines’ turns to be a most wanted thing for people as it is their destination in life. For western philosophers especially classic philosophers such as Socrates, Plato, Aristoteles, Epikuros argue that happiness is the highest level achieved by someone. The sciences developed by the philosophers eventually aim to reach inner peace (eudiomonia). The happiness could be achieved by good deeds, peaceful heart and a healthy body. In the Qur’an, the word ‘happy’ is translated from sa’id, meanwhile the word ‘sad’ as antonym of happy is translated from Saqiy. Other words used in the Qur’an to describe happines are falah, najat and najah. In the Qur’an’s view, there are at least 6 ways to gain happiness in life: First, believing that there must be solution after troubles. Second, thanking Allah for favors granted, pleasure, patience, and resignation for any disaster. Third, forgive others if they make mistakes upon you. Fourth, staying away from prejudice. Fifth, avoid habitual grumpy when facing or hit something. Sixth, reducing the desire worldly with zuhud and qona’ah.